Thick blood film examination for Plasmodium falciparum malaria has reduced sensitivity and underestimates parasite density - Bejon, P; Andrews, L; Hunt-Cooke, A; Sanderson, F; Gilbert, S; Hill, A (BioMed Central, 2006)
Background: Thick blood films are routinely used to diagnose Plasmodium falciparum malaria. Here, they were used to diagnose volunteers exposed to experimental malaria challenge. Methods: The frequency with which blood films were positive at given parasite densities measured by PCR were analysed. The poisson distribution was used to calculate the theoretical likelihood of diagnosis. further in vitro studies used serial dilutions to prepare thick films from malaria cultures at know parasitaemia. Results: Even in expert hands, thick blood films were considerably less sensitive than might have been expected from the parasite numbers measured by quantitative PCR. In vitro work showed that thick films prepared from malaria cultures at known parasitaemia consistently underestimated parasite densities. Conclusion: It appears large numbers of parasites are lost during staining. This limits their sensitivity, and leads to erroneous estimates of parasite density.